(untitled) (Journal of the College of Basic Education, 2022)
The modest interest of cultural institutions and musical researchers in the production of Iraqi artists is considered by documenting and diagnosing the stages of the lyrical and musical career as a cultural heritage of Iraq that must be preserved from loss or extinction.